Penyuluhan Penggunaan Dan Pembuatan Pupuk Organik Cair Dari Bahan Baku Lokal - Aditya, Dipa; Utomo, Budi; Hidayati, Sri; Ikka, Ni Dewi Ambal; Kusumawati, Nur Farida; Ismawati, Wiji; Yahya, Wahyu Mauval (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Counseling on the use and manufacture of liquid organic fertilizers from local raw materials is a community service activity conducted by University lecturer Maj. Gen. Sungkono, especially at the Faculty of Agriculture in Tinggar Hamlet, Tinggarbuntut Village, Bangsal district, Mojokerto Regency. The goal is to improve pet owners ' understanding of organic pet food as a last resort to ensure that the relatively low prices and prevalence of fertilizer stocks in the village make pet owners the majority. The method used is an experimental method. As a result, workers are able to produce goods using local materials and maximize the amount of daily labor available so that they are eager to master new skills or knowledge, such as practical skills, in rice fields and village halls.